Exploring the Effect of Arrest Across a Domestic Batterer Typology. (January 2015) - Johnson, Richard R.; Goodlin‐Fahncke, Wendi
Abstract While arrest is a common intervention utilized in intimate partner violence, it is not known if this strategy affects all types of offenders equally. The present study used data from three of the Spousal Assault Replication Program (SARP) studies to examine the deterrent effect of arrest on four different batterer subtypes (those identified by Holtzworth‐Munroe and Stuart, 1994) among a sample of 2, 412 heterosexual male batterers. The results indicated that arrest increased the recidivism of IPV for two of the batterer subtypes (generally violent/antisocial and low‐level antisocial subtypes), suggesting the need for pre‐trial protection of victims.